G54 Impact of pneumococcal conjugate vaccines on pneumococcal meningitis in england and wales, 2000 – 2016. (12th March 2018) - Oligbu, G; Djennad, A; Collins, S; Sheppard, CL; Fry, NK; Borrow, R; Andrew, NJ; Ladhani, S
Abstract : Introduction: The introduction of pneumococcal conjugate vaccines (PCV) was associated with reduction in incidence of invasive pneumococcal disease (IPD) especially IPD caused by the vaccine serotypes. Its impact on meningitis in the United Kingdom has not been assessed. Methods: Public Health England conducts enhanced surveillance for IPD and provides a national reference service for serotyping pneumococcal isolates in England and Wales. Data were extracted for isolates from confirmed IPD cases between 1 st July 2000 and 30th June 2016, covering the 2000/01 to 2015/16 epidemiological years. Incidence rate ratio (IRR) and case fatality rate (CFR) were calculated. Multivariable logistic regression was used to calculate the odds of meningitis and assessed its association with death. Results: There were 80 313 laboratory-confirmed IPD cases over the 16 year surveillance period, including 4160 cases (4.9%) with meningitis. Of the 4108 with reported age, 1611 (39.2%) cases were reported in children aged <5 y, 1729 (42.1%) in 5–64 year-olds and 768 (18.7%) cases in 65+year olds. This compares with 8324 (10.5%), 32 297 (40.6%) and 38 999 (49.0%) of 79 620 non-meningitis cases during the same period, respectively (p<0.001). PCV7 introduction in September 2006 had no impact on the overall incidence of pneumococcal meningitis (0.55/100, 00 during 2000/01–2005/06 vs 0.56/100, 000 during 2008/09–2009/10) because of serotype replacement disease. PCV7 replacement with PCV13 in April 2010, however, led to a 48% (95% CI: 38%–62%) reduction in pneumococcal meningitis incidence by 2015/16, whilst meningitis cases due to non-PCV13 serotypes remained static. The overall CFR was 17.5% (631/3, 611, increasing from 10.7% (150/1408) in <5 y to 17.3% (262/1517) in 5–64 y and 31.9% (219/686) in 65+year olds. This compared with 3.6% (254/716), 10.8% (3, 235/30, 090) and 30.6% (11, 292/36, 907) for non-meningitis for the same age groups, respectively. CFR for meningitis due to PCV7 serotypes (130/916, 14.2%) compared to PCV13 (143/793, 18.0%) or non-PCV13 serotypes (290/1, 534, 18.9%). Among meningitis cases, serotype 8 was associated with increased odds of death (aOR, 2.91; 95% CI: 1.79 to 4.71; p<0.0001) Conclusions: The impact of PCV on pneumococcal meningitis has been less prominent than for other IPD presentations and case fatality remains high; a different strategy is, therefore, required to reduce the burden and outcomes of pneumococcal meningitis.